2012
DOI: 10.1159/000338821
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Bony Cochlear Nerve Canal on Hearing in Patients with Congenital Unilateral Sensorineural Hearing Loss

Abstract: This study was designed to evaluate the dimensions of the bony cochlear nerve canal (BCNC) in congenital unilateral sensorineural hearing loss (USNHL) patients with normal inner ears, and to analyze the correlation between BCNC and hearing status. Medical records and temporal bone computed tomography (TBCT) findings of 380 patients who visited Seoul National University Hospital between January 1999 and December 2007 were reviewed retrospectively. The length and width of the BCNC at the fundus of the internal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In a previous study, we evaluated the BCNC length and width in normal inner ears: 1.07 mm and 2.38 mm, respectively. In cases of congenital unilateral sensorineural hearing loss, the BCNC length and width in affected inner ears were significantly smaller than those in normal inner ears [ 1 ]. The mean width in the affected inner ears in our previous study was 1.58 mm; other investigators have reported mean widths of 1.12 mm and 1.0 mm [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study, we evaluated the BCNC length and width in normal inner ears: 1.07 mm and 2.38 mm, respectively. In cases of congenital unilateral sensorineural hearing loss, the BCNC length and width in affected inner ears were significantly smaller than those in normal inner ears [ 1 ]. The mean width in the affected inner ears in our previous study was 1.58 mm; other investigators have reported mean widths of 1.12 mm and 1.0 mm [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has suggested that the lower limit of normal BCNC width is 2.10 mm; this was obtained by subtraction of the standard deviation from the mean value in normal hearing inner ears [ 1 ]. Thus, the mean BCNC width in normal patients is higher than 2.0 mm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the bony cochlear nerve canal (BCNC) evaluation system developed by Fatterpekar et al [10], relationships between BCNC parameters and both hearing level and the presence of the cochlear nerve were established [11]. In our study, the width of the BCNC at the fundus of the internal auditory canal was determined in axial slices of temporal bone computed tomography images, at the point where it was maximal in contiguous sections, by measuring the distance between the inner margins of the bony wall at the mid-portion.…”
Section: Methodsmentioning
confidence: 99%